Digital Video EssentialsTM : Shoot, Transfer, Edit, Share. - Sadun, Erica (John Wiley & Sons, 2006)
The Perfect Companion for Your Digital Video Camera Digital video brings the power of studio production to the personal computer. With just a video camera, a computer, and the proper software, you can create your own innovative and unique movies for personal or business use.